Análisis energético y exergético de un ciclo de potencia brayton de multigeneración utilizando energía termosolar concentrada CSP como fuente de calor en Colombia (2021)
Concentrated solar thermal energy (CSP) has proven to be a novel alternative for the generation of useful energy within the group of renewable energies. In the present work a detailed Energetic and Exergetic analysis of a multi-generation system that uses solar thermal energy for the production of electricity and refrigeration is carried out. The system is integrated by a Parabolic Cylinder Solar Collector Field (CCSCP) used to provide useful thermal power to a Closed Brayton Cycle (CBC), an Organic Rankine Cycle (CRO) used to recover the residual heat from the Brayton cycle and supply part of the power generated in a Vapor Compression Refrigeration (CRCV) cycle.